Establishment of open web platform based on 3D head model for product adaptability analysis and evaluation. Issue 12 (December 2022) - Li, Zhelin; Deng, Xianghong; Lee, Yu-Chi; Jiang, Lijun; Yu, Guangzheng; Fan, Jiaxu
Abstract: With improved living conditions, the demand for wearable products has increased, particularly for headwear. Traditionally, the dimensions of headwear products are designed according to 1D anthropometric data, such as head length, width, and eye width. However, this design method, applied to fit the 3D human head, results in differences in adaptability, which affect the wearing comfort of the user. Hence, this study aimed to develop an aided design platform based on a three-dimensional standard head shape to evaluate the virtual wearing of headwear products and adaptability testing. Specifically, a WebGL-based service, named the Chinese Headwear Adaptability Testing (CHAT) platform, was established. Validation and user studies were then conducted using an eye massager device. After the product was redesigned according to evaluation by the proposed system, the results show that the comfort and adaptability of the redesigned eye massager were significantly improved. The findings suggest that using the CHAT platform to design headwear products can help achieve a better wearing fit for the products. Abstract : Chinese head; Percentile; Acupoint; Headwear product; Adaptability.